(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Hepatitis A is on the rise died of illness​ step of times by learning the bride. Hepatitis A is anthroponosis, a common viral disease that belongs to the group of infectious intestinal infections, transmitted by the fecal-oral mechanism. A hepatitis virus enteroviruses type and picornaviruses to his family belong to being diameter according to this, it is equal to 27 nm. Hepatitis A virus resistance to high temperature, ethers, disinfectants ensures its long survival in the external environment. It can be stored at low temperature for months and sometimes years. As a result of the resistance to these disinfectants, in some cases viruses can pass through the blockages in the water treatment facilities and enter the water supply networks, causing disease.